Study of Towing Lug Strength in 300 feet Barge at Docking Process - Andi Mursid Nugraha Arifuddin; Amalia Ika Wulandari; Mohammad Ardha Wiku Wicaksono (Department of Naval Architecture - Diponegoro University, 2023)
Currently, the docking of ships or barges has been dominated by the airbag system by relying on the pull of the winch. For the Kalimantan area, the barge is generally pulled using a winch during docking. The structures that play a role when pulling the barge are towing brackets, slings, pulleys, and winches. In this paper, the towing lug will be the object of special discussion regarding its structural strength performance. The towing Lug model used when towing is in the form of an asymmetrical lobe. Two towing brackets are placed on the left and right sides of the bow barge. This towing lug sometimes damaged during towing, so it is necessary to simulate the strength of the towing lug using the finite element method (FEM). A 300 feet Barge is simulated with a total weight (W) of 1200 Tons. The towing lug design structure is made with 3 kinds of models with a varying number of layers and plate thickness. The towing lug design sample used in the existing shipyard is called model 1. While the other modifications to the 2 towing lug structures are called model 2 and model 3. Towing brackets are simulated using a computer with the help of Ansys software. The towing bracket's tensile angle is also varied to obtain a more attractive strength value. The variations of the pull angles used in this simulation are 80°, 83°, 85°, 87° and 90°. From the simulation results, it is obtained that the deformation values in each model show an insignificant level of change. In general, the simulation results also show stress values for each variation that tend to be safe and can be applied when the barge is towed to the dry dock. All equivalent stress values in each condition are still below the material yield stress. However, among the various simulations there are 2 types of conditions that experience stress values that exceed the class allowable stress